Microstructure of NWA 4435 meteorite - Szurgot, Marian; Polański, Krzysztof (Politechnika Łódzka, 2008)
Elemental composition, mineral composition and microstructure of NWA 4435 meteorite found in 2006 has been studied by analytical electron microscopy and optical microscopy. It was established that the main meteorite minerals: olivines, pyroxenes, troilite, and graphite identified in the sample represent extraterrestrial minerals typical of carbonaceous chondrites. Chemical and mineral composition, petrologic type of chondrules, their abundance and sizes, the presence of troilite, and abundance of oxidized iron phases confirm CV3 class of this chondrite.

Badano skład chemiczny i mineralny oraz mikrostrukturę meteorytu NWA 4435. Zanalizowano chondry i ciasto skalne meteorytu. Obecność chondr, troilitu, inkluzji wysokotemperaturowych oraz tekstura próbki świadczą o pozaziemskim pochodzeniu badanej skały i przynależności tego meteorytu do chondrytów węglistych klasy CV3.
Mikrostruktura meteorytu NWA 4435